Case Report: Review of CT Findings and Histopathological Characteristics of Primary Liver Carcinosarcoma - Huang, Lu; Lu, Lijian (Frontiers in Genetics, 2021)
Objectives: The aim of the present study was to describe the computed tomography (CT) characteristics of primary liver carcinosarcoma (PLCS) and to explore the pathological basis for the diagnosis of primary hepatocellular carcinoma sarcoma. Methods: Three male patients with PLCS were included in the present retrospective research and the age was ranged from 52 to 63 years old. The plain CT scan and third-stage enhancement scan were performed on patients. The pathological characteristics were analyzed. Stomachache was the main clinical symptoms of the three patients. Cirrhosis background was confirmed in one patients and chronic Hepatitis B background was confirmed in other 2 patients. Results: According to the results of CT, the inner diameter of the tumors was ranged from 8.6 to 27.0 cm. Fibrous pseudocapsule around the tumor tissues was observed in 2 patients. Tumor tissues from all 3 patients were composed of sarcomatous and carcinomatous components. For carcinomatous components, hepatocellular carcinoma was observed in 1 patient and cholangiocarcinoma was observed in other 2 patients. For sarcomatous components, angiosarcoma was observed in 2 patients and malignant fibrous histiocytoma was observed in another 1 patient. The tumor tissues were visualized as heterogeneous low density with large sheets of necrotic cystic lesions or thick-walled areas of multilocular cystic lesions using the plain CT scan. Edge-to-center filling and strengthening lesions, mild to moderate enhanced parenchyma at arterial phase, and isodense between the tumor parenchyma and the surrounding liver parenchyma at the portal vein phase or delayed phase were observed using the third-stage enhancement scan. Conclusions: CT characteristics observed in the present study were of great benefit for the diagnosis of PLCS.